Questioning mobility as a service: Unanticipated implications for society and governance. (January 2020) - Pangbourne, Kate; Mladenović, Miloš N.; Stead, Dominic; Milakis, Dimitris
Highlights: The dominant MaaS rhetoric advances a promise of freedom to users that cannot be delivered. There are equity implications associated with various unanticipated consequences and these require mitigation. Promises of 'efficiency' are not possible without government intervention. Abstract: In this paper we focus on the development of a new service model for accessing transport, namely Mobility as a Service (MaaS) and present one of the first critical analyses of the rhetoric surrounding the concept. One central assumption of one prevalent MaaS conceptualization is that transport services are bundled into service packages for monthly payment, as in the telecommunication or media service sectors. Various other forms of MaaS are being developed but all tend to offer door-to-door multi-modal mobility services, brokered via digital platforms connecting users and service operators. By drawing on literature concerned with socio-technical transitions, we address two multi-layered questions. First, to what extent can the MaaS promises (to citizens and cities) be delivered, and what are the unanticipated societal implications that could arise from a wholesale adoption of MaaS in relation to key issues such as wellbeing, emissions and social inclusion? Second, what are de facto challenges for urban governance if the packaged services model of MaaS is widely adopted, and what are the recommended responses? To address these questions, we begin by considering the evolution of intelligent transport systems that underpin the current vision of MaaS and highlight how the new business model could provide a mechanism to make MaaS truly disruptive. We then identify a set of plausible unanticipated societal effects that have implications for urban planning and transport governance. This is followed by a critical assessment of the persuasive rhetoric around MaaS that makes grand promises about efficiency, choice and freedom. Our conclusion is that the range of possible unanticipated consequences carries risks that require public intervention (i.e. steering) for reasons of both efficiency and equity.